Measurement of the W(+/-)Z production cross section and limits on anomalous triple gauge couplings in proton-proton collisions at root s=7 TeV with the ATLAS detector - Onofre, A. (2012)
This Letter presents a measurement of W±ZW±Z production in 1.02 fb−1 of pp collision data at View the MathML sources=7 TeV collected by the ATLAS experiment in 2011. Doubly leptonic decay events are selected with electrons, muons and missing transverse momentum in the final state. In total 71 candidates are observed, with a background expectation of View the MathML source12.1±1.4(stat.)−2.0+4.1(syst.) events. The total cross section for W±ZW±Z production for Z/γ⁎Z/γ⁎ masses within the range 66 GeV to 116 GeV is determined to be View the MathML sourceσWZtot=20.5−2.8+3.1(stat.)−1.3+1.4(syst.)−0.8+0.9(lumi.) pb, which is consistent with the Standard Model expectation of View the MathML source17.30.8+1.3 pb. Limits on anomalous triple gauge boson couplings are extracted.